Reduction in field emergence and seedbank density of Galinsoga quadriradiata and other weeds after contrasting false seedbed strategies in organic vegetable fields. (16th April 2019) - De Cauwer, B; De Cuypere, T; De Ryck, S; Delanote, L; DeWaele, K; Willekens, K; Reheul, D
Summary: Mechanical weed control in low competitive, organic vegetable production systems is challenging, particularly in fields with large populations of Galinsoga spp. (Asteraceae). Various false seedbed techniques are used prior to crop planting or sowing to prevent weed emergence, albeit with variable success. This study investigated the impact of machinery type (flamer, hoe and harrow), number of passes (2 and 4), tillage depth (1–4 cm) and intensity (double and single hoeing, and hoeing with or without additional harrowing) on weed emergence and seedbank density in 0–5 cm topsoil of organic vegetable fields. False seedbed machinery that did not or minimally disturb the soil was most appropriate for preventive control of Galinsoga quadriradiata (Hairy galinsoga) and total weed seeds, with reductions in seedling emergence up to 99% and 73%, respectively, for flaming, and 74% and 67%, respectively, for 1 cm deep hoeing, 1 month after false seedbed creation. Compared with 1 cm deep hoeing, 1 cm deep harrowing was 16% less effective in the control of emerged seedlings, while flaming was highly effective in preventing weed seedling emergence, even after a low number of passes. Tillage intensity was less important than tillage depth for the reduction in weed emergence and seedbank density. Overall, tillage was more effective for seedbank reduction than flaming.